Acute Effect of Topical Menthol on Chronic Pain in Slaughterhouse Workers with Carpal Tunnel Syndrome: Triple-Blind, Randomized Placebo-Controlled Trial. (14th September 2014) - Sundstrup, Emil; Jakobsen, Markus D.; Brandt, Mikkel; Jay, Kenneth; Colado, Juan Carlos; Wang, Yuling; Andersen, Lars L.
Abstract : Topical menthol gels are classified "topical analgesics" and are claimed to relieve minor aches and pains of the musculoskeletal system. In this study we investigate the acute effect of topical menthol on carpal tunnel syndrome (CTS). We screened 645 slaughterhouse workers and recruited 10 participants with CTS and chronic pain of the arm/hand who were randomly distributed into two groups to receive topical menthol (Biofreeze) or placebo (gel with a menthol scent) during the working day and 48 hours later the other treatment (crossover design). Participants rated arm/hand pain intensity during the last hour of work (scale 0–10) immediately before 1, 2, and 3 hours after application. Furthermore, global rating of change (GROC) in arm/hand pain was assessed 3 hours after application. Compared with placebo, pain intensity and GROC improved more following application of topical menthol (P = 0.026 andP = 0.044, resp.). Pain intensity of the arm/hand decreased by −1.2 (CI 95%: −1.7 to −0.6) following topical menthol compared with placebo, corresponding to a moderate effect size of 0.63. In conclusion, topical menthol acutely reduces pain intensity during the working day in slaughterhouse workers with CTS and should be considered as an effective nonsystemic alternative to regular analgesics in the workplace management of chronic and neuropathic pain.